The Effect of Individual and Regional Characteristics on Commuting (Study on Gerbangkertosusila Area, East Java) - Setyanti, Axellina Muara; Ashar, Khusnul; Susilo, Susilo (International Journal of Social and Local Economic Governance, 2021)
Differences in economic opportunity, such as the difference between interregional wage gaps triggered the migration of workers to areas with higher wage rates, as happened in Gerbangkertosusila Area, East Java. In addition to economic factors such as wages, educational factor, age, marital status, unemployment and population number in many theories are also expressed to influence the tendency to migrate. On the other hand the denser urban area gives rise to commuting. Therefore, this study aims to determine the effect of individual and regional characteristics on labor migration in Gerbangkertosusila Area. Using multilevel binary logistic regression, the findings show that the variables significantly affecting commuting decision are age, marital status, secondary and higher education, wage gap and open unemployment rate. Furthermore, workers with a hingher tendency to commute are workers with individual characteristics of male, young, unmarried, highly educated, and self-employed, and with regional characteristics of smaller wage gap, higher open unemployment rate in the origin, and lower population on destination.